2015
DOI: 10.1136/bmjopen-2015-007766
|View full text |Cite
|
Sign up to set email alerts
|

Antibodies to myelin oligodendrocyte glycoprotein in idiopathic optic neuritis

Abstract: ObjectivesTo investigate the differences of clinical features, cerebrospinal fluid (CSF), MRI findings and response to steroid therapies between patients with optic neuritis (ON) who have myelin oligodendrocyte glycoprotein (MOG) antibodies and those who have seronegative ON.SettingWe recruited participants in the department of neurology and ophthalmology in our hospital in Japan.MethodsWe retrospectively evaluated the clinical features and response to steroid therapies of patients with ON. Sera from patients … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
58
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 72 publications
(65 citation statements)
references
References 15 publications
7
58
0
Order By: Relevance
“…As suggested by previous results (Table 3), MOG-IgG positive patients may present with a clinical diagnosis of idiopathic ON 9,11 or NMOSD 6,10 . The MOG-IgG patients frequently have recurrent or bilateral ON and the male predominance contrasts with the female predominance in MS.…”
Section: Discussionmentioning
confidence: 78%
“…As suggested by previous results (Table 3), MOG-IgG positive patients may present with a clinical diagnosis of idiopathic ON 9,11 or NMOSD 6,10 . The MOG-IgG patients frequently have recurrent or bilateral ON and the male predominance contrasts with the female predominance in MS.…”
Section: Discussionmentioning
confidence: 78%
“…This showed not only a marked reduction in relapse rate, and AQP4-antibody titers, but also a reduction in pain severity scores [42 && ]. In addition it has been shown that, when compared with those NMO patients without either AQP4 or MOG antibodies, those with MOG autoantibodies also report a significantly higher level of pain [37]. These data suggest a link between pain and the inflammatory or neuropathological effect of autoantibodies in NMO.…”
Section: Neuromyelitis Opticamentioning
confidence: 91%
“…In a large proportion of patients (around 70%) autoantibodies against the water channel aquaporin-4 (AQP4) are found [36]; a smaller proportion of those patients who are negative for AQP4-antibodies has antibodies against another molecule myelin oligodendrocyte glycoprotein (MOG) [37], but in these cases the disease is less longstanding. AQP4-antibody positive NMO patients can experience loss of vision and paralysis, but pain is a particularly common feature of NMO with more than 80% of sufferers experiencing this symptom, often persisting even when the disease is relatively quiescent and intractable to conventional pain killers [38 & ].…”
Section: Neuromyelitis Opticamentioning
confidence: 99%
“…Among anti-AQP4 antibody-seronegative NMO patients, 21.1% were reported to have anti-MOG antibodies (4). In a recent report of patients with idiopathic optic neuritis, 27.6% were positive for MOG antibodies and 3.4% were positive for AQP4; these patients often showed optic pain and high CSF levels of myelin basic protein (6). Although our patient showed cerebral involvement with contrast enhancement lesions, myelin basic protein was not elevated in her CSF, and no oligoclonal bands were present.…”
Section: Discussionmentioning
confidence: 99%
“…The pathomechanisms of these antibody-positive demyelinating disorders are unknown. Moreover, cerebral brain magnetic resonance imaging (MRI) abnormalities of patients with optic neuritis with anti-MOG antibodies occur less frequently than optic nerve lesions (6). We herein report the case of a patient who had optic neuritis with a long-term follow-up, anti-MOG antibodies, and abnormalities in the cerebral white matter and brainstem.…”
Section: Introductionmentioning
confidence: 91%